Evidence for Progressive Microstructural Damage in Early Multiple Sclerosis by Multi-Shell Diffusion Magnetic Resonance Imaging. (1st April 2019) - Toschi, Nicola; De Santis, Silvia; Granberg, Tobias; Ouellette, Russell; Treaba, Constantina A.; Herranz, Elena; Mainero, Caterina
Abstract: In multiple sclerosis (MS), it would be of clinical value to be able to track the progression of axonal pathology, especially before the manifestation of clinical disability. However, non-invasive evaluation of short-term longitudinal progression of white matter integrity is challenging. This study aims at assessing longitudinal changes in the restricted (i.e. intracellular) diffusion signal fraction (FR) in early-stage MS by using ultra-high gradient strength multi-shell diffusion magnetic resonance imaging. In 11 early MS subjects (disease duration ≤ 5 years), FR was obtained at two timepoints (one year apart) through the Composite Hindered and Restricted Model of Diffusion, along with conventional Diffusion Tensor Imaging metrics. At follow-up, no statistically significant change was detected in clinical variables, while all imaging metrics showed statistically significant longitudinal changes ( p < 0.01, corrected for multiple comparisons) in widespread regions in normal-appearing white matter (NAWM). The most extensive longitudinal changes were observed in FR, including areas known to include a large fraction of crossing fibers. Furthermore, FR was also the only metric showing significant longitudinal changes in lesions that were present at both time points ( p = 0.007), with no significant differences found for conventional diffusion metrics. Finally, FR was the only diffusion metric (as compared to Diffusion Tensor Imaging) that revealed pre-lesional changes already present at baseline. Taken together, our data provide evidence for progressive microstructural damage in the NAWM of early MS cases detectable already at 1-year follow-up. Our study highlights the value of multi-shell diffusion imaging for sensitive tracking of disease evolution in MS before any clinical changes are observed. This article is part of a Special Issue entitled: SI: MRI and Neuroinflammation . Highlights: We use the CHARMED diffusion model to assess restricted signal fraction (FR) in 11 multiple sclerosis patients at 1 year follow-up. The most extensive longitudinal changes were observed in FR, including areas known to include a large fraction of crossing fibers. FR was the only metric showing significant longitudinal changes in lesions that were present at both time points. FR was the only metric that revealed pre-lesional changes already present at baseline. We evidence for progressive microstructural damage in the NAWM of early MS cases detectable already at 1-year follow-up.